La Teoría de los Sistemas y de las Mediaciones. Enfoques posibles para los estudios de la comunicación organizacional en Cuba - Hilda Saladrigas Medina (Mediaciones Sociales, 2007)
Organizational communication is a young discipline that is advancing its consolidation in Cuba. Its studies and researches have been historically marked by the positivist paradigm, but are now changing towards new theoretical-methodological perspectives. In the frame of the Systems Theory, with a closer approach to the paradigm of complexity, and the Theory of Social Mediation developed by Professor and researcher Manuel Martín Serrano (enriched by the Latin-American perspectives) constitute possible theoretical approaches which may enrich the studies that are being made on this topic, at the same time that it can validate its own suppositions.